Radiographic Measurements of the Cardiac Silhouette in Healthy Blue-Fronted Amazon Parrots (Amazona aestiva) - Silva, Jeana P. [UNESP]; Castiglioni, Maria C. R. [UNESP]; Doiche, Danuta P. [UNESP]; Vettorato, Michel C. [UNESP]; Fogaça, Jéssica L. [UNESP]; Mamprim, Maria J. [UNESP]; Rahal, Sheila C. [UNESP]; Vulcano, Luiz C. [UNESP] (Association of Avian Veterinarians (AAV), 2020)
The objective of this investigation was to determine radiographic measurements, without chemical restraint, of the cardiac silhouette in 34 healthy, adult blue-fronted Amazon parrots (Amazona aestiva) of unknown sex with a mean body weight of 393 g. The birds were fasted 3 hours before the radiographic examinations. Three thoracic radiographic views (ventrodorsal, right lateral, and left lateral) were obtained from each bird for assessment. There was no significant statistical difference between right and left radiographic measurements. The mean values of the measurements in the ventrodorsal views were heart width of 21.04 mm and coelomic cavity width of 50.61 mm. The mean values of the measurements in the lateral views were left heart length of 23.44 mm, right heart length of 23.40 mm, left sternal length of 65.69 mm, and right sternal length of 65.03 mm. A strong correlation and ratio of 43% between the heart width and coelomic cavity width and a moderate correlation and ratio of 36% between the heart length and sternal length were observed. In conclusion, the radiographic measurements of the cardiac silhouette in healthy blue-fronted Amazon parrots can be obtained without chemical restraint. The values obtained can be used to assist in the detection of cardiomegaly or microcardia in blue-fronted Amazon parrots.
Keywords: Amazona aestiva; avian; blue-fronted Amazon parrot; cardiovascular system; imaging diagnostic; psittacine bird; radiography